Keanekaragaman Ikan di Kawasan Sungai Barito Desa Lepasan Kabupaten Barito Kuala - Elmara Frieday Mulyawan; Mahrudin Mahrudin; Nurul Hidayati Utami (Program of Biology Education, Universitas Lambung Mangkurat, 2026)
The Barito River is one of the major aquatic ecosystems in South Kalimantan, known for its high biodiversity potential. Human activities around the river, such as settlement expansion and fishing, may affect habitat conditions and fish community structures. This study aimed to investigate the diversity of fish species in the Barito River area, specifically in Lepasan Village, Barito Kuala Regency. Sampling was conducted using a 50-meter rengge gill net under two water conditions—morning and afternoon—at a river depth of 13 meters during high tide. Sampling sites were selected purposively based on representative aquatic conditions. The results identified 14 fish species belonging to five families: Cyprinidae (7 species), Bagridae (3 species), Siluridae (2 species), Polynemidae (1 species), and Pristolepididae (1 species). The Shannon-Wiener diversity index values were H’ = 2.48 in the vegetated zone and H’ = 2.39 in the residential zone, indicating a moderate level of species diversity. This study provides an overview of fish diversity in the Barito River at Lepasan Village, serving as a reference for future aquatic resource management and conservation efforts.